Who's master of your domain? web services security in an unfriendly world. - Hollar, Rickland
W.C. Fields once said, "The practice of keyhole-listening is usually confined to hotels and boarding houses. It is absolutely indefensible to stoop so low. If the transom is not ajar, remember there are plenty of other rooms in the building." Hackers on the Web can take a similarly cavalier attitude-surfing from site to site until they find one whose "transoms are ajar." The question for you is whether yours are among them.